Hemerocallis citrina Baroni leaf total phenol alleviates depressive-like behaviors via modulating “microbiota-gut-brain” axis in chronic unpredictable mild stress -induced rats - Wang, Yanping; Jia, Yanjun; Zhao, Wanning; Shao, Yazhou; Zhang, Zeyu; Chen, Huiru; Qian, Shuangxi; Hu, Fangdi (Frontiers in Pharmacology, 2025)
BackgroundDepression is closely associated with dysfunction of the microbiota-gut-brain axis (MGBA). Total phenol from Hemerocallis citrina leaves (HLTP) exhibits antidepressant potential, but its role in relieving depression by regulating MGBA remains uninvestigated.MethodsIn this study, the chronic unpredictable mild stress (CUMS) method was used to establish a rat model of depression to investigate the ameliorative effects of HLTP on depression.ResultsBehavioral and pathological results showed HLTP improved weight loss, increased sucrose preference, reduced forced swimming immobility time, novel-suppressed feeding latency, open field movement trajectory, and alleviated hippocampal CA1 neuronal damage in CUMS-depressed rats. At 10, 20, and 40 mg/kg, HLTP increased dopamine (DA), noradrenaline (NE), 5-hydroxytryptamine (5-HT), interleukin-10 (IL-10), brain-derived neurotrophic factor (BDNF), and cAMP response element-binding protein (CREB) in the brain. It also decreased the inflammatory factor (TNF-α and IL-1β) in the brain, as well as corticotropin-releasing hormone (CRH), adrenocorticotropic hormone (ACTH), and corticosterone (CORT) in serum and brain. HLTP modulated gut microbiota diversity and reversed CUMS-induced alterations in 15 bacterial taxa, including Alloprevotella and Monoglobus. Additionally, HLTP reversed 63 CUMS-induced abnormal serum metabolites, primarily affecting tryptophan metabolism, niacin and nicotinamide metabolism, and porphyrin metabolism. Significant correlations were observed among gut microbial composition, serum metabolite levels, biochemical indices, and behavioral outcomes.ConclusionHLTP exerts antidepressant effects in CUMS-induced rats by modulating the MGBA. It enhances metabolic function, reduces neuroinflammatory damage, restores neurotrophic factor levels, suppresses hyperactivity of the hypothalamic-pituitary-adrenal axis, and corrects monoamine neurotransmitter deficiencies, collectively contributing to the attenuation of depression-related symptoms.